Google, Amazon, and Beyond: Creating and Consuming Web Services - Nakhimovsky, Alexander (Apress, 2012)
While many books are focused on the underlying technologies of web services and others are dedicated to providing web services, few books show how to consume web services. Google, Amazon, and Beyond: Creating and Consuming Web Services provides a thorough review of the technologies and techniques for connecting client applications to services of all kinds.